Communicative skills formation during sports training of boxers - Kolesnik, I. S.; Gatin, F. A.; Osipov, D. A. (The Russian Journal of Physical Education and Sport, 2016)
The level of communicative abilities and skills development is one of the important components of a boxer`s sports training, the style of behavior at ring depends on the degree of these abilities and skills formation. Rational relations setting between a sportsman and trainers, partners, opponents influences sports qualification increase, forms the ability to an objective estimation of own technical-tactical, physical, intellectual training. Material. The article offers a prospective direction of this problem solution by means of the methodology creation of communicative skills, self-analysis, ability to form relations during sports training formation. Research methods: scientific and scientific-methodical literature analysis, specialists` progressive pedagogical experience summarizing - practitioners in sports training of boxers; observations, pedagogical experiment, testing, static handling of the material. Results. The article is about the importance of specially organized activity, directed at communicative skills formation in sports sphere. One of professional qualities of a teacher is the ability to communicate, to form interrelations, which provide respect, trust and it makes this ability one of the leading qualities in the system of sportsmen sports training. An important element of the created methodology is the skills of self-analysis formation, the ability to create interrelations with sportsmen, trainer, opponents, people in general. It provides the skills formation of a critical attitude and estimation of own abilities of training and competitive activity and the search for the ways of weak sides of sports training elimination. The boxers from the experimental group managed the target mindsets of a trainer, more successfully fulfilled the algorithms of techniques, their competitive performances were more stable. Conclusion. As the results of the pedagogical experiment showed, the process of communicative skills and personal qualities formation is not spontaneous; its effectiveness is mainly conditioned by a purposeful, considered system of upbringing influences within the whole educational-training and competitive environment. The received results proved the necessity to form communicative skills, the ability to create interrelations with the team members, opponents, with people around of different age, in case of obligatory support of an experienced trainer.